Imelda - Diaz, Ramona S. ([New York] Cinediaz, 2003)
Explores the persona of former Philipine First Lady, Imelda Marcos.
Produced and directed by Ramona S. Diaz.
Keywords: Marcos, Imelda Romualdez -- 1929-.; Presidents' spouses -- Philippines -- Biography; Biographical videos